Immittance response alginate-polyvinyl alcohol bio-polymer blend electrolytes doped with ammonium iodide - M. A. H., Nizam; A. F., Fuzlin; Ahmad Salihin, Samsudin (Tech Science Press, 2025)
This work explores the dielectric and electrochemical properties of solid biopolymer blend electrolytes (SBEs) based on a combination of alginate and polyvinyl alcohol (PVA), doped with varying concentrations of ammonium iodide (NH4I). The SBEs were synthesized using the solution casting method, and their ac conductivity exhibited an optimal value of 1.01 × 10−5 S · cm−1 at 25 wt.% NH4I. Detailed dielectric and modulus spectroscopy analyses revealed distinctive trends in relation to NH4I concentration, suggesting complex dielectric relaxation behavior. The universal power law (UPL) analysis identified the Small Polaron Hopping (SPH) mechanism as the dominant conduction process in the optimal sample. These results demonstrate that NH4I-doped alginate-PVA SBEs possess favorable electrochemical properties, positioning them as potential candidates for energy storage and ionic transport devices.